Developmental and gender influences on executive function following concussion in youth hockey players. (15th October 2015) - Lax, Ilyse D.; Paniccia, Melissa; Agnihotri, Sabrina; Reed, Nick; Garmaise, Evan; Azadbakhsh, Mahdis; Ng, Justin; Monette, Georges; Wiseman-Hakes, Catherine; Taha, Tim; Keightley, Michelle
Abstract: Background : Concussion is the most common athletic injury in youth who are simultaneously undergoing rapid developmental changes in the brain, specifically the development of executive functions (EF). The developing brain is more vulnerable to concussive injury with a protracted and different trajectory of recovery than that of adults. Thus, there is a critical need to enhance understanding of how concussion affects EF in youth. Objective : To investigate the effects of age, gender and concussion history (i.e. concussion incidence, recency, severity) on EF in youth hockey players. Methods : This 3-year cross-sectional and longitudinal multiple cohort study examined data from 211 hockey players of 8–15 years of age. Mixed-effects modelling was used to examine the influence of age, gender and concussion on EF in youth athletes. Findings : Baseline analyses revealed significant age and gender effects on measures of EF. Multiple effects of concussion history on measures of cognitive flexibility ( F = 2.48, p = 0.03) and psychomotor speed ( F = 2.59, p = 0.04) were found. Implications : This study highlights the impact of age, gender and concussion on EF in youth. These findings provide foundational knowledge to better manage cognitive sequelae following sports-related concussion.